Szimuláció a társadalomtudományokban - Kovács, Balázs; Takács, Károly (Szociológiai Szemle, 2024)
Empirical studies in the social sciences often investigate the effects of specific factors and neglect the underlying explanatory mechanisms that lead from the factor to the effect. Considering the explanatory variables they rarely scrutinize individual action and its relation to macro-phenomena. On the other hand, a common flaw of the theoretical social sciences is that they have an oversimplified view about individual actors, they treat society as a homogenous group of individuals, and they overlook the embeddedness and complexity of (social) action. Computer simulation may be a useful tool to eliminate these shortcomings and to bridge the gap between empirical and theoretical social sciences. This study, on these grounds, stands for the usefulness of simulation-methodology in social sciences, by discussing its abilities and constraints.